ACPA-negative rheumatoid arthritis: From immune mechanisms to clinical translation - Li, Ketian; Wang, Min; Zhao, Lidan; Liu, Yudong; Zhang, Xuan (EBioMedicine, 2022)
The presence of anti-citrullinated protein autoantibodies (ACPA) is a hallmark feature of rheumatoid arthritis (RA), which causes chronic joint destruction and systemic inflammation. Based on ACPA status, RA patients can be sub-grouped into two major subsets: ACPA-positive RA (ACPA+ RA) and ACPA-negative RA (ACPA– RA). Accumulating evidence have suggested that ACPA+ RA and ACPA– RA are two distinct disease entities with different underlying pathophysiology. In contrast to the well-characterized pathogenic mechanisms of ACPA+ RA, the etiology of ACPA– RA remains largely unknown. In this review, we summarized current knowledge about the primary drivers of ACPA– RA, particularly focusing on the serological, cellular, and molecular aspects of immune mechanisms. A better understanding of the immunopathogenesis in ACPA– RA will help in designing more precisely targeting strategies, and paving the road to personalized treatment. In addition, identification of novel biomarkers in ACPA– RA will substantially promote early treatment and improve the outcomes.